The knowledge, attitude and practice of health and skincare therapists at accredited clinics around South Africa with regard to nutrition - Rademeyer, Catharina Elizabeth (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2010.